Hippotherapy in Autism Spectrum Disorder: clinical benefits and the relevance of the veterinarian’s role in equine welfare – An integrative review (Research, Society and Development, 2025)
Objective: To analyze the clinical benefits of hippotherapy in Autism Spectrum Disorder (ASD) and highlight the essential role of veterinarians in ensuring equine welfare during therapeutic sessions. Methods: integrative review conducted according to Whittemore and Knafl, aligned with PRISMA 2020. Searches were conducted in SciELO, BDENF, CAPES, and PubMed (2019–2022). From 38 identified studies, 8 met eligibility criteria. Results: findings indicated improvements in balance, motor coordination, communication, attention, and social interaction among individuals with ASD, as well as relevant information about equine welfare, including mild lameness, behavioral alterations, and need for physiological monitoring. Conclusion: hippotherapy is an effective intervention, while veterinarians are essential for guaranteeing equine health, safety, and performance.